Hubungan Kadar Asam Urat dengan Kadar Gula Darah pada Wanita Usia Subur Prediabetes - Santy Irene Putri; Asruria Sani Fajriah; Prima Soultoni Akbar; Aris Widiyanto; Joko Triatmojo (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2021)
Uric acid is the end product of purine metabolism. In conditions of high levels, uric acid enters cells and acts as an oxidant, and acts as an independent risk factor and predicts the incidence of type 2 diabetes mellitus. This study aimed to analyze the relationship between uric acid levels and blood sugar levels in women of childbearing age prediabetes. This was an observational analytic study with a cross-sectional design. This study was conducted in Malang City. A sample size of 100 women of childbearing age were selected using simple random sampling technique. The dependent variable was blood sugar levels women of childbearing age prediabetes. The independent variable is uric acid levels. The data were collected by examining uric acid levels and fasting blood sugar levels in the study subjects. Data were analyzed using Pearson correlation. Based on the study results, it was found that uric acid levels were associated with blood sugar levels in prediabetic women of childbearing age (r = 0.21, p = 0.039) and were statistically significant. There is a relationship between uric acid levels and blood sugar levels in prediabetic women of childbearing age.